Electrical equipment for measurement, control and laboratory use. EMC requirements. Particular requirements. Test configurations, operational conditions and performance criteria for insulation monitoring devices according to IEC 61557- 8 and for equipment for insulation fault location according to IEC 61557-9 Part 2-4, (11th June 2021) - British Standards Institution,
No abstract available